Moscow University Computational Mathematics and Cybernetics - Moiseev, Evgenii I.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
The journal publishes original papers of high scientific value in all areas of computational mathematics and cybernetics at the interface between applied mathematics, numerical computation, and applications. Papers that describe and analyze new computational techniques for solving scientific or engineering problems are especially welcome.
Keywords: Mathematics; Mathematics, general